2019
DOI: 10.1002/cbf.3466
|View full text |Cite
|
Sign up to set email alerts
|

The role of microRNAs in acute lymphoblastic leukaemia: From biology to applications

Abstract: MicroRNAs (miRNAs) that are characterized by small, noncoding RNA have an essential role in the pathogenesis of human diseases, including cancer. Furthermore, miRNAs, as a new paradigm of epigenetic regulators, play an important role in normal development and cellular function. This literature review summarizes the recurrent mechanism of gene regulation through miRNAs and, consequently, the impact of regulated genes on different cellular processes, including proliferation, metastasis, prognosis, and apoptosis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 89 publications
(100 reference statements)
0
7
0
Order By: Relevance
“…miR-126 originally recognized as endothelial-specific miRNA plays an essential role in angiogenesis and vascular integrity [25] and has been shown to function as a critical tumor suppressor in various solid tumors [26,27]. In contrast, it has been demonstrated that miR-126 is aberrantly expressed and reported to possess a oncogenic role in core binding factor leukemia [28,29]. miR-126 has been implicated in the progression of non-small-cell lung cancer, and the expression levels of miR-126 have been found to be significantly downregulated in non-small-cell lung cancer [30].…”
Section: Discussionmentioning
confidence: 99%
“…miR-126 originally recognized as endothelial-specific miRNA plays an essential role in angiogenesis and vascular integrity [25] and has been shown to function as a critical tumor suppressor in various solid tumors [26,27]. In contrast, it has been demonstrated that miR-126 is aberrantly expressed and reported to possess a oncogenic role in core binding factor leukemia [28,29]. miR-126 has been implicated in the progression of non-small-cell lung cancer, and the expression levels of miR-126 have been found to be significantly downregulated in non-small-cell lung cancer [30].…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs can also regulate genes involved in signaling pathways, such as the Notch, MAPK, and PI3K/AKT pathways, that are common amongst many types of leukemias [ 54 ]. For instance, it has been reported that the overexpression of miR-125b and miR-331 is associated with myeloid leukemia and ALL, respectively [ 36 , 55 ]. In addition, it has been observed that the ectopic expression of let-7c promotes granulocytic differentiation in AML [ 40 ], the low expression of miR-22 modifies the differentiation of monocytes in normal and leukemic states [ 40 ], and changes in the miR-17-92 cluster expression have resulted in the appearance of lymphoproliferative disorders [ 42 ].…”
Section: Mirnas and Hematopoiesismentioning
confidence: 99%
“…Besides limitless replicative potential , cancer cells are also featured by the evasion of programmed cell death . In B-cell precursor ALL, up-regulated miR-187-5p induces Bcl-2 protein, resulting in the apoptosis resistance of cells [ 53 ], while silencing of miR-127 by promoter hypermethylation contributes to increased expression level of Bcl-6 in bladder cancer [ 54 ]. The oncogenic miR-155 is implicated in sustained angiogenesis of tumors by down-regulation of von Hippel–Lindau (VHL) tumor suppressor protein [ 55 ].…”
Section: Implication Of Mirnas In Carcinogenesis and Leukemogenesismentioning
confidence: 99%